ISOLASI SENYAWA ALKALOID DARI DAUN SIDAGURI (Sida rhombifolia L.) - Sovia Lenny; Tonel Barus; Evi Yoana S (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2010)
The secondary metabolite compound was isolated from sidaguri (Sida rhombifolia L.) leaves. The diethylether extract was subjected to a column chromatography with a mixture of chloroform:methanol (7:3) was obtained as amorf (59 mg). The FT-IR and 1H-NMR spectrum indicated the isolated compound was alkaloid compound.Keywords : Sidaguri (Sida rhombifolia L.), column chromatography, alkaloid